An exploratory study of change mechanisms for ambivalence reduction in young adult cyclical relationships - Washburn-Busk, Michelle (Kansas State University, 2017)
Cyclical relationships (where multiple break-ups and renewals have occurred) have been characterized as being in a state of “stable instability” (Vennum & Johnson, 2015), and emerging adulthood has been deemed a critical phase of relational development and learning, as well as a time marked by instability (Arnett 2000; 2007). While the research continues to expand on what we know about the concurrent and enduring risks for distress associated with relationship cycling, little is known about what change mechanisms/interventions may reduce these risks, or how helping professionals (therapists, relationship educators) can specifically assist young adults in cyclical relationships. After conducting five focus groups, researchers found specific factors that promote or detract from “decision-making resiliency”, or DMR. Specific points of intervention for professionals working with cyclical relationships to promote DMR are discussed, which included identity development, communication, power/control dynamics and intentionality. Building off of what is known about the nuances of cyclical relationships, this study aims to inform assessments and intervention(s) that would help bolster resilience and decision-making skills in cyclical couples (or couples who have slid into relationships and are, thus, at risk for cycling) in an effort to reduce further distress.
Keywords: Cycling; On-again off-again; Relationship; Ambiguity